Analisis Pengelolaan Modal Kerja, dan Leverage Terhadap Profitabilitas Melalui Good Corporate Governance - Kharis Triyogi; Ira Setiawati; Ika Indriasari (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This research aims to analyze Working Capital Management and Leverage on Profitability Through Good Corporate Governance (Empirical Study of Consumer Cyclicals Sector Companies Listed on the Indonesian Stock Exchange (BEI) for the 2020 – 2022 Period. The research population is all listed Consumer Cyclicals sector companies on the Indonesia Stock Exchange (BEI) for the period 2020 - 2022 with a total of 139 companies, the sample that has been determined in this research is 31 companies using non-probability sampling techniques with the Purposive Sampling method. Data analysis in this research uses the SmartPLS program. Hypothesis testing using the SEM-PLS approach. The results of the analysis and discussion of Working Capital Management have an effect on Profitability, Leverage has no effect on Profitability, Good Corporate Governance has an effect on Profitability, indirectly Working Capital Management has no effect on Profitability through Good Corporate Governance, and indirectly h Leverage has no effect on Profitability through Good Corporate Governance in Consumer Cyclicals Sector Companies Listed on the Indonesia Stock Exchange (BEI) for the 2020 – 2022 Period.